Galileo’s Error: Foundations for a New Science of Consciousness by Philip Goff - Williams III, George Robert (Journal of Scientific Exploration, 2020)
A new book by Philip Goff, Galileo’s Error: Foundations for a New Science of Consciousness, accomplishes a number of notable things. Perhaps foremost, Goff provides an excellent overview of the debate on consciousness for a wide audience with little or no background in philosophy. He guides the reader through the various frameworks that include dualism, physicalism, and panpsychism. Goff’s Galileo’s Error thus provides an excellent introduction for anyone with interest in the growing science of consciousness. However, Goff does promote a particular angle. As a professor of philosophy at Durham University, Goff has followed the arguments of David Chalmers and others that materialistic explanations ultimately fail to explain consciousness. Like Chalmers, Professor Goff believes that in order to find a successful explanation, we will likely choose a direction that takes consciousness as fundamental in some sense. Toward this end, Goff has also become a leading advocate for panpsychism, the view that the ultimate particles that constitute our world have a mental aspect. However, Goff’s book also provides an important contribution regarding the philosophy of science. By examining science’s development at an early stage, especially Galileo’s role, Goff addresses an important aspect to the current debate on consciousness. And attention on the role of philosophy in science is also important, given the recent bashing philosophy has been handed by some scientists. To make progress on consciousness, Goff argues we will likely need to do some hard thinking and reexamine some of our core assumptions. He provides many examples to demonstrate that often what is required is time spent thinking and rethinking the problem, perhaps in contrast to voices who emphasize just getting on with the lab or field work. But what exactly is Galileo’s error, you might be wondering? Most of us recognize that Galileo played a pivotal role in ushering in the scientific revolution through emphasizing testing theories by observation. But as Goff notes, central to Galileo’s contribution was his emphasis on specific characteristics that could be quantified—size, shape, location, and motion. And this meant removing such qualities that we experience directly, such as taste and smell, out of the domain of inquiry. That is, Galileo pragmatically sought to remove inherently subjective matters that could not fit into a quantitative framework. This has brought mixed fruit. Science, as conceived by Galileo, is widely seen as one of the most successful developments in the history of thought. The focus on subjects that could be analyzed mathematically has led to true triumphs in understanding as well as abundant applications that have transformed the physical world.